National budget for 1970 : Finland (Helinski : Ministry of Finance Economic Department, 1970)
The Economic Survey published as an appendix to the Government's budget proposal for 1970 included forecasts concerning economic development in 1970
Summarised in English by Jaakko Railo
osc 21/05/2019
Ref.
Keywords: Budgets; Finland